On vector bundles for a Morse decomposition of LCP^n - Ottosen, Iver (MATHEMATICA SCANDINAVICA, 2017)
We give a description of the negative bundles for the energy integral on the free loop space LCP^n in terms of circle vector bundles over projective Stiefel manifolds. We compute the mod p Chern classes of the associated homotopy orbit bundles.